Endovascular Management of Varicose Veins: A Review of Literature - Singhal, Soumil; Uthappa, Mangerira Chinnappa (Journal of Clinical Interventional Radiology ISVIR, 2019)
Venous insufficiency of the lower limb is a common condition characterized by a spectrum of symptoms, including bulging leg veins, pain, swelling, and ulceration. Various treatment options are available; however, the newer endovascular options are easy, highly effective, safe, and quick in relieving symptoms. Endovascular treatment options include thermal ablation, mechanicochemical ablation, and foam sclerotherapy. This review article briefly describes various scoring systems used in varicose veins, the role of imaging, different management techniques, and guidelines proposed in the management of this condition.
Keywords: varicose vein; intervention; radiology